Improving vehicular delay-tolerant network performance with relay nodes - Soares, V.N.G.J. (2009)
Vehicular Delay-Tolerant Networking (VDTN) is an extension of the Delay-Tolerant Network (DTN) architecture concept to transit networks. VDTN architecture handles non-real time applications, exploiting vehicles to enable connectivity under unreliable scenarios with unstable links and where an end-to-end path may not exist. Intuitively, the use of stationary store-and-forward devices (relay nodes) located at crossroads where vehicles meet them and should improve the message delivery probability. In this paper, we analyze the influence of the number of relay nodes, in urban scenarios with different numbers of vehicles. It was shown that relay nodes significantly improve the message delivery probability on studied DTN routing protocols.